Sword art online : Early and late - Kawahara, Reki (Sword Art Online, 2016)
"The game of death took its toll on every player in a different way--when one turns up dead on the fifty-seventh floor, the game is afoot, and it is up to Asuna and Kirito to crack the case--also the story of how Kirito got his Excalibur sword in Alfheim"--